Employees' opinion in Tehran University of Medical Sciences (TUMS) on usability of in-service electronic training courses. - Alavi, Sayedeh Shohreh; Sarmadi, Mohammad Reza (Iranian Journal of Medical Education)
Introduction: Usability is one of the issues that must be considered in designing effective e-learning courses. The aim of this study was evaluating employees' opinion in Tehran University of Medical Sciences (TUMS) about usability of in-service electronic training courses. Methods: This descriptive cross sectional study was conducted on employees in Tehran University of Medical Sciences, working in the fields of health care, finance and logistics, cultural and educational affairs. They had participated in electronic in-service training courses. Random stratified sampling was used to select 651 eligible employees to complete a 21 item questionnaire on usability, learning ability, and satisfaction based on Likert scale. Content validity and reliability of the questionnaire were confirmed in a pilot study and by Cronbach's alpha coefficient, respectively. Data were analyzed by statistical tests such as Student's T test and One Way ANOVA with Bonferroni Post Hoc test based on the type of variable in SPSS 16. Results: The mean score and SD of the employees viewpoints regarding learning ability was 3.4 ± 0.5, satisfaction 3.7 ± 0.7, and usability 3.2 ± 0.5. Based on the results, variables of job field, location of computer access, ability to use computer, internet access, and motivation to participate in e-courses showed a significant correlation with usability. Conclusion: The findings showed that the usability of e-courses from the viewpoint of the university employees seems acceptable. Employees' computer knowledge and their accessibility to software and hardware were influential to usability of educational courses.